The mutationally activated Met receptor mediates motility and metastasis - Jeffers, Michael (The National Academy of Sciences, 1998)
Mutations in Met have been identified in human papillary renal carcinomas. We have shown previously that these mutations deregulate the enzymatic activity of Met and that NIH 3T3 cells expressing mutationally activated Met are transformed in vitro and are tumorigenic in vivo. In the present investigation, we find that mutant Met induces the motility of Madin-Darby canine kidney cells in vitro and experimental metastasis of NIH 3T3 cells in vivo, and that the Ras-Raf-MEK-ERK signaling pathway, which has been implicated previously in cellular motility and metastasis, is constitutively activated by the Met mutants. We also report that transgenic mice harboring mutationally activated Met develop metastatic mammary carcinoma. These data confirm the tumorigenic activity of mutant Met molecules and demonstrate their ability to induce the metastatic phenotype.